Transcriptome analysis of larval immune defence in the lamprey Lethenteron japonicum. Issue 94 (November 2019) - Zhang, Taotao; Zhang, Mimi; Xu, Ting; Chen, Shangwu; Xu, Anlong
Abstract: The lamprey is a primitive jawless vertebrate that occupies a critical phylogenetic position, and its larval stage represents the major portion of its life cycle [1]. Lamprey larvae have been proven to be an important model organism for studying numerous biological problems, such as the immune system, due to their unique biological features [2]. In addition, early-stage larvae have never been obtained from the wild [3]; therefore, it is necessary to establish artificial breeding of lampreys in the laboratory. However, during early development, the larvae exhibit susceptibility to saprolegniasis, and the immune responses of lamprey larvae to this infection remain poorly understood. Here, we established a model of fungal infection in lamprey larvae and then used RNA sequencing to investigate the transcript profiles of lamprey larvae and their immune responses to Saprolegnia ferax . Among the profiled molecules, genes involved in pathogen recognition, inflammation, phagocytosis, lysosomal degradation, soluble humoral effectors, and lymphocyte development were significantly upregulated. The results were validated by analysis of several genes by quantitative real-time PCR and whole-mount in situ hybridization. Finally, we performed a Western blot for VLRs in infected and uninfected lampreys. This work not only provides an animal model for studying fungal infection but also suggests a molecular basis for developing defensive strategies to manage Saprolegnia ferax infection. Highlights: We established a model of fungal infection in lamprey larvae. We used RNA sequencing to investigate their immune responses to Saprolegnia ferax. This work suggests a molecular basis for developing defensive strategies to manage Saprolegnia ferax infection.